Secondary syphilis with stage III HIV in an adolescent deaf male with a history of sexual relationship with men: a case report - Tritya Mudita; Ni Made Dwi Puspawati; I Gusti Ayu Sattwika; Andrew Yoshihiro Wirya (Bali Dermatology and Venereology Journal, 2021)
Introduction: Syphilis is an infection caused by Treponema pallidum of the spirochaete family.Case: A 19-year-old Balinese came with a complaint of red spots on the palms of the hands and feet one month ago. The patient has a hearing disability and is currently enrolled in a special-needs school in Denpasar. VDRL examination with reactive results with titer 1:256 and TPHA reactive with TPHA titer 1:5120. The patient received benzathine penicillin G 2.4 million units intramuscularly. Significant improvement was obtained, and the serological test was decreased.Discussion: Syphilis transmits through sexual contact, vertically from pregnant women to their fetuses, through needle sharing. People with hearing disabilities and adolescents are considered vulnerable as objects of harassment and sexual violence.Conclusion: People with disabilities and adolescents are vulnerable to sexually transmitted diseases. Information on reproductive health and sexually transmitted diseases need to be more readily available for people with disabilities. Secondary syphilis therapy with a single dose of benzathine penicillin is effective from clinical or serological observations.